You bet your life : the burdens of gambling - Isaacs, Neil D., 1931- (University Press of Kentucky, 2001)
We are a nation of gamblers: pari-mutuel wagering at horse tracks; blackjack in Las Vegas; the NCAA basketball office pool; even day trading on the internet. Gambling is both our national pastime and our predominant cultural metaphor -- play the field; beat the odds; take a chance on love. Yet gambling poses serious risks to individuals and to society as a whole. Neil Isaacs -- sports historian, licensed clinical social worker, English professor, and a gambler himself for more than fifty years -- seeks to shatter the myths interfering with our understanding of gambling addiction, its causes, an.